ANALISIS PENERAPAN PROGRAM K3 SEBAGAI UPAYA PENCAPAIAN ZERO ACCIDENT DI PT X (DEPARTEMEN PRODUKSI) - Nanda Agung Hermawan; Puji Isyanto; Neni Sumarni (Halu Oleo University, 2025)
The purpose of this study was to determine the extent of the implementation of occupational safety and health (K3) and to determine the programs for implementing occupational safety and health (K3) in PT. X. This study uses a qualitative method, where data collection is carried out through interviews, so that it can dig deeper into the implementation of occupational safety and health (K3) in optimising employee performance. Participants in this study were employees as the main informants, K3 officers and production managers as key informants and an HR expert. The results of this study indicate that PT. X production department has so far had an Occupational Health and Safety program that has been implemented consistently and continuously, through training, simulation of dangerous conditions, safety campaigns, safety talks, K3 socialisation, and provision of PPE. The conclusion of this study, PT. X production department has implemented the K3 program optimally with zero work accidents, even though there are individual obstacles; some employees are negligent in accepting the K3 program in the work area, which is an obstacle in implementing efforts to achieve zero accidents.